Hadith #449 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
In the mosque l asked Ibn Abi Hadrad to pay the debts which he owed to me and our voices grew louder. Allah’s Messenger (ﷺ) heard that while he was in his house. So he came to us raising the curtain of his room and said, “O Ka`b!” I replied, “Labaik, O Allah’s Messenger (ﷺ)!” He said, “O Ka`b! reduce your debt to one half,” gesturing with his hand. I said, “O Allah’s Messenger (ﷺ)! I have done so.” Then Allah’s Apostle said (to Ibn Abi Hadrad), “Get up and pay the
Grade: Sahih

Hadith #1747 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) stood beside me at Al-Hudaibiya and the lice were falling from my head in great number. He asked me, “Have your lice troubled you?” I replied in the affirmative. He ordered me to get my head shaved. Ka`b added, “This Holy Verse:–‘And if any of you is ill, or has ailment in his scalp (2.196), etc. was revealed regarding me. “The Prophet (ﷺ) then ordered me either to fast three days, or to feed six poor persons with one Faraq (three Sas) (of dates), or to sl
Grade: Sahih

Hadith #1750 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) saw him (i.e. Ka’b) while the lice were falling on his face.
Grade: Sahih

Hadith #2961 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
Whenever the Prophet (ﷺ) returned from a journey in the forenoon, he would enter the Mosque and offer two rak`at before sitting.
Grade: Sahih

Hadith #3986 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
That Allah’s Messenger (ﷺ) saw him with the lice falling (from his head) on his face. Allah’s Messenger (ﷺ) said, “Are your lice troubling you? Ka`b said, “Yes.” Allah’s Messenger (ﷺ) thus ordered him to shave his head while he was at Al-Hudaibiya. Up to then there was no indication that all of them would finish their state of Ihram and they hoped that they would enter Mecca. Then the order of Al-Fidya was revealed, so Allah’s Messenger (ﷺ) ordered Ka`b to feed six poor per
Grade: Sahih

Hadith #4014 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
The Prophet (ﷺ) came to me at the time of Al-Hudaibiya Pledge while lice were falling on my face. He said, “Are the lice of your head troubling you?” I said, “Yes.” He said, “Shave your head and fast for three days, or feed six poor persons, or slaughter a sheep as sacrifice.” (The sub-narrator, Aiyub said, “I do not know with which of these three options he started.”)
Grade: Sahih

Hadith #4015 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
We were in the company of Allah’s Messenger (ﷺ) at Al-Hudaibiya in the state of Ihram and the pagans did not allow us to proceed (to the Ka`ba). I had thick hair and lice started falling on my face. The Prophet (ﷺ) passed by me and said, “Are the lice of your head troubling you?” I replied, Yes.” (The sub-narrator added, “Then the following Divine Verse was revealed:– “And if anyone of you is ill or has an ailment in his scalp, (necessitating shaving) must pay a ransom (Fida) o
Grade: Sahih

Hadith #4591 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
It was said, “O Allah’s Messenger (ﷺ)! We know how to greet you, but how to invoke Allah for you?” The Prophet said, “Say: Allahumma salli ala Muhammadin wa’ala `Ali Muhammaddin, kama sallaita ‘ala all Ibrahim, innaka Hamidun Majid.”
Grade: Sahih

Hadith #5289 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
that a slave girl of theirs used to shepherd some sheep at Si’a (a mountain near Medina). On seeing one of her sheep dying, she broke a stone and slaughtered it. Ka`b said to his family, “Do not eat (of it) till I go to the Prophet (ﷺ) and ask him, or, till I send someone to ask him.” So he went to the Prophet (ﷺ) or sent someone to him The Prophet (ﷺ) permitted (them) to eat it.
Grade: Sahih

Hadith #5429 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
The Prophet (ﷺ) said, “The example of a believer is that of a fresh tender plant, which the wind bends lt sometimes and some other time it makes it straight. And the example of a hypocrite is that of a pine tree which keeps straight till once it is uprooted suddenly.
Grade: Sahih

Hadith #5451 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
The Prophet (ﷺ) passed by me while I was kindling a fire under a (cooking) pot. He said, “Do the lice of your head trouble you?” I said, “Yes.” So he called a barber to shave my head and ordered me to make expiation for that.”
Grade: Sahih

Hadith #5486 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
The Prophet (ﷺ) came to me during the period of Al-Hudaibiya, while I was lighting fire underneath a cooking pot and lice were falling down my head. He said, “Do your lice hurt your?” I said, “Yes.” He said, “Shave your head and fast for three days or feed six poor persons or slaughter a sheep as a sacrifice:”
Grade: Sahih

Hadith #6464 - Sahih al-Bukhari - K'ab bin 'Amr bin 'Ubbad (Sahih al-Bukhari)
I came to the Prophet (ﷺ) and he said to me, “Come near.” So I went near to him and he said, “Are your lice troubling you?” I replied, “Yes.” He said, “(Shave your head and) make expiation in the form of fasting, Sadaqa (giving in charity), or offering a sacrifice.” (The sub-narrator) Aiyub said, “Fasting should be for three days, and the Nusuk (sacrifice) is to be a sheep, and the Sadaqa is to be given to six poor persons.”
Grade: Sahih